Media effects as health research: how pediatricians have changed the study of media and child development. Issue 2 (2nd April 2016) - Bickham, David S.; Kavanaugh, Jill R.; Rich, Michael
Abstract: Although the study of media and children has long been interdisciplinary, child health researchers and pediatric journals have joined their social science counterparts to investigate media effects over the past several decades. Research on how media use influences child health and development has increased exponentially in pediatric journals between the early 1990s and the present. Communication and psychology scholars have begun to publish their media effects work in medical journals. Health researchers, who previously synthesized existing science on media effects into policy statements and recommendations, now conduct original research. In this article, we review this transformation by documenting publication patterns in journals from different disciplines and discussing possible explanations for the shift. We consider the benefits and challenges presented by this evolution in the study of media and children, and postulate about how it has shaped the future direction of research and policy.